Social Welfare Department Sarawak / Nor Salwan Hossen - Hossen, Nor Salwan (Universiti Teknologi MARA, Sarawak, 2014)
In March 1993, Social Welfare Department has been upgraded from the Welfare Division of the Ministry of Social Development Sarawak. The function of this department has been developed and placed as important agencies under the Ministry of Social Development and Urbanization Sarawak. In the beginning, the Welfare Division was established to address the welfare by taking over the function from Sarawak Welfare Council in General Assistance by assisting victims of disasters, as well as expand its charitable activities by providing the necessary services in accordance with the changing times.